4 - Situating African Indigenous Ideas within Conventional Learning as an Impetus for Knowledge Construction in Africa - Omotosho, Babatunde Joshua (Journal of Higher Education in Africa, 2022)
Literature regarding knowledge production reveals that Africa can do better than its present state through the exploration and installation of homegrown ideas detached from the Western hold on its academy. This article contributes to this debate by exploring the place of indigenous knowledge within the academy and the challenges facing its popularity within the continent. The article further provides suggestions on how indigenous and conventional orthodox knowledge can cohere towards a more pragmatic knowledge production that can propel Africa’s development.